2017
DOI: 10.3389/fcimb.2017.00275
|View full text |Cite
|
Sign up to set email alerts
|

Differential Substrate Usage and Metabolic Fluxes in Francisella tularensis Subspecies holarctica and Francisella novicida

Abstract: Francisella tularensis is an intracellular pathogen for many animals causing the infectious disease, tularemia. Whereas F. tularensis subsp. holarctica is highly pathogenic for humans, F. novicida is almost avirulent for humans, but virulent for mice. In order to compare metabolic fluxes between these strains, we performed 13C-labeling experiments with F. tularensis subsp. holarctica wild type (beaver isolate), F. tularensis subsp. holarctica strain LVS, or F. novicida strain U112 in complex media containing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
(128 reference statements)
0
20
0
Order By: Relevance
“…Whilst these subtle trends found in tetracycline-treated flies could be attributed to low bacterial loads (rather than immune activation), hyperglycaemia and triglyceride depletion were not seen in tetracycline-treated imd mutants, demonstrating that immune costs—rather than bacterial load—were responsible. However, that we do see triglyceride depletion in normal-food imd flies, suggests that at least part of this phenotype is pathogen-driven, possibly resulting from host triglyceride usurpation by the bacteria ( 36 38 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Whilst these subtle trends found in tetracycline-treated flies could be attributed to low bacterial loads (rather than immune activation), hyperglycaemia and triglyceride depletion were not seen in tetracycline-treated imd mutants, demonstrating that immune costs—rather than bacterial load—were responsible. However, that we do see triglyceride depletion in normal-food imd flies, suggests that at least part of this phenotype is pathogen-driven, possibly resulting from host triglyceride usurpation by the bacteria ( 36 38 ).…”
Section: Discussionmentioning
confidence: 70%
“…Francisella spp. preferentially use glucose as a carbon source (38,42). It has also been shown that F. tularensis cannot use glycogen as a carbon source (43); thus, if glycogen depletion were the result of bacterial consumption of nutrients, the expected pathway would be via bacterial depletion of free sugar triggering host glycogenolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This process is required for intracellular replication of F. tularensis but failure to replicate due to inhibition of macroautophagy could be rescued with the addition of excess nonessential amino acids or pyruvate [4]. In addition, the pathogen also employs differential metabolite fluxes that varies between Francisella species, suggesting that the different utilization of substrates could be related to host specificity and virulence of Francisella [68,69]. In addition, the pathogen overrides host restriction of iron [70].…”
Section: How Intracellular Pathogens Overcome Host Nutrient Restrictionmentioning
confidence: 99%
“…This is the case, for example, of intracellular pathogens that are commonly faced with a diverse set of host nutrients in infected tissues. In these cases, bacteria have been shown to adapt to this situation by the simultaneous exploitation of plastic and flexibles nutrient utilization strategies [15][16][17][18][19] .…”
mentioning
confidence: 99%